Edukasi Perawatan Tali Pusat pada Bayi Baru Lahir untuk Mencegah Infeksi di Desa Padelegan (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2026)
Umbilical cord infection remains one of the major causes of morbidity and mortality among newborns, particularly in areas where knowledge and health practices are still limited. Padellegan Village is one of the regions where some mothers continue to practice traditional cord care methods, such as using herbal mixtures or non-sterile materials, which increases the risk of omphalitis. Initial situation analysis indicates that 40–60% of postpartum mothers are not yet familiar with the principles of clean and dry cord care (dry cord care), and access to accurate health information is still limited. Based on this condition, education on umbilical cord care is essential to improve mothers’ and health cadres’ understanding and skills in preventing neonatal infections. This community service activity focuses on providing evidence-based education regarding safe cord care techniques, infection risk factors, and danger signs that need to be recognized. Padellegan Village was selected due to the high need for maternal–neonatal health education and the low level of community knowledge related to cord care. This activity is expected to bring positive changes, such as improved maternal behavior in performing proper cord care, reduced use of unhygienic traditional methods, and strengthened roles of health cadres in monitoring neonatal health. Enhancing appropriate cord care practices can reduce the risk of infection in newborns, thereby contributing to improving the overall health status of the community in Padellegan Village.